Sosialisasi DBD berbasis Statistik Kesehatan dan Agama di Pondok Pesantren Raudhatul Ulum Campurejo Bojonegoro - Choiri, Moh. Miftahul; Nurdiansyah, Denny; Barata, Mula Agung; Abidin, Zainul; Nasirudin, M. (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The dengue prevention socialization program at Pondok Pesantren Raudhatul Ulum, Bojonegoro, was conducted to anticipate the spread of dengue fever during the rainy season. Factors such as population density, health promotion, and community attitudes influence dengue cases, while public knowledge has yet to show a significant impact. The program aimed to educate students on the importance of healthy living and maintaining environmental cleanliness to prevent dengue fever. Methods: The program was designed in four stages: socialization, technology implementation, mentoring and evaluation, and sustainability. The focus was on education, the use of simple tools, and enhancing the capacity of health cadres. Sustainability was ensured through integration into the boarding school’s routine agenda, active partner involvement, and collaboration with health institutions. Results: The dengue prevention socialization program at Pondok Pesantren Raudhatul Ulum, Bojonegoro, on November 11, 2024, utilized a Participatory Learning and Action (PLA) approach that actively engaged students. The activities included educating the students on the 4M Plus method, distributing guidebooks, and providing larvicide. The main challenge was ensuring students' consistency in implementing preventive measures, while sustainability opportunities were supported through regular monitoring. Conclusions: The dengue prevention socialization program at Pondok Pesantren Raudhatul Ulum successfully increased students' knowledge and participation through the 4M Plus method and an interactive approach, although consistent implementation of preventive measures still requires further monitoring.